Readability and Suitability of COPD Consumer Information - Kathryn Fullmann; David F. Blackburn; Mark E. Fenton; Holly Mansell (Canadian Respiratory Journal)
Background. Information leaflets have been shown to positively or negatively impact adherence, depending on their content. The objective of this study was to perform an appraisal of the consumer information provided in COPD inhaler monographs. Methods. COPD inhalers were identified from the Health Canada Drug Product Database. Medication information and instructions for inhaler use were analyzed for readability by seven formulas, with an acceptability threshold of grades 6–8. Three researchers rated suitability using a modified Suitability Assessment of Materials (SAM) tool and assessed leaflets for explicit warnings. Results. Twenty-six inhalers with a COPD indication were evaluated. Medication information sections were rated as “difficult to read” or “hard,” and 85% (22/26) had a reading level above grade 8. The instructions for inhaler use were rated as “easy” or “fairly easy” to read and 63% (16/26) met the threshold by all formulas. While all leaflets achieved superior suitability ratings, extreme warnings included risk of premature death (n=12), risks of serious injury (n=26), serious interactions (n=26), and statements that convey a serious consequence to therapy (n=26). Conclusion. While COPD information leaflets in Canada performed well in terms of readability and suitability, overemphasis on side effects, warnings, and precautions may contribute to patient fear and nonadherence.